Eu também sou dona de casa: reimaginando a cozinha como lugar de memória, autonomia e expressão artística - Paz, Lívia Chagas da (2025)
This artistic research emerges from the intersection of art, autobiogeography, and feminism to question the place of women artists in creative spaces. I center the kitchen as a focal point for reflections and practices, revisiting my trajectory, which begins with watercolor self-portraits and, years later, expands into ceramics. Throughout this process, I investigate how domestic logic—historically associated with women—can be redefined through artistic practice. In this context, I engage with authors and artists such as Virginia Woolf, Silvia Federici, bell hooks, Martha Rosler, and Mierle Ukeles to discuss memory, care, and the transmission of female knowledge. Drawing on Manoela dos Anjos Afonso Rodrigues, Lauren Fournier, and Gloria Anzaldúa, I develop a methodology that intertwines autobiogeography and autotheory within artistic research. The resulting ceramic works include Bolsa (2024), which examines self-representation; Conjugação (2024) and Casamento (2023), which explore the kitchen as a site of affective and power negotiations; and Quitandas (2024), in which I transform family recipes into ceramic pieces, activating memories and ancestral knowledge passed down through generations. Thus, I highlight the political and poetic potential of everyday practices, proposing the kitchen not only as a space of resistance but as a place for reinvention and expanded creation